Estudo do sono, fun????o pulmonar e qualidade de vida em pacientes com miastenia gravis auto imune adquirida - Oliveira, Ezequiel Fernandes de (2014)
Introduction: Autoimmune myasthenia gravis is an chronic disease inflammatory characterized by progressive weakness of the skeletal muscles due to a change in the synapses between the nerves and muscle fibers. The manifestations of the respiratory system are generally attributed to the weakness of the diaphragm and other accessory muscles of ventilation leading to breathlessness. Among these manifestations, we highlight the onset of sleep-disordered breathing (SDB) due to weakening of the muscles of the oropharynx. Objectives: To verify the lung function, respiratory muscle strength, and physiological variables during sleep in patients with myasthenia gravis clinically stable. Methods: This is a prospective cross-sectional descriptive study, following a study protocol previously published. Patients were recruited consecutively from the Setor de Investiga????o de Doen??as Neuromusculares of the Universidade Federal de S??o Paulo in accordance with the eligibility criteria, and referred to the Sleep Laboratory of Universidade Nove de Julho, S??o Paulo (Brazil). Results: The study included 18 patients The mean age of 42,66??10,91 (15 women). Regarding lung function only two patients had a restrictive ventilatory pattern. The maximum ventilatory pressures observed were considerably reduced in most patients when compared to reference values. Regarding sleep, highlight observe a significant decrease in oxyhemoglobin saturation, reduced REM sleep time, increased stage NREM3, considerable increase of apnea and hypopnea per hour and a high risk for obstructive sleep apnea. Discussion: Data on sleep-related disorders in patients with Autoimmune myasthenia gravis in the literature are scarce and inconclusive, with few studies using basal nocturnal polysomnography. Conclusion: Clinically stable patients with autoimmune myasthenia gravis have a high prevalence of sleep respiratory disorders and a significant reduction in maximal inspiratory and expiratory pressures with reduced quality of life.